2009
DOI: 10.1136/gut.2008.167353
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type III alpha I is a gastro-oesophageal reflux disease susceptibility gene and a male risk factor for hiatus hernia

Abstract: Background and objectives:Gastro-oesophageal reflux disease (GORD) is a common gastrointestinal disorder with a genetic component. Our aim was to identify genetic factors associated with GORD.Patients and methods:Four separate patient cohorts were analysed using a step-wise approach. (1) Whole genome linkage analysis was performed in 36 families. (2) Candidate genes were tested for GORD association in a trio cohort. (3) Genetic association was replicated in a case–control cohort. We also investigated genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…The collagen chains are encoded by at least 17 genes. The collagen type III α1 (COL3A1) gene encodes type III collagen and might be associated with hiatus hernia formation 38 . Collagen type XXIII α1 (COL23A1) gene is probably linked to scrotal hernia development in pigs 39 .…”
Section: Studies On Collagen Synthesismentioning
confidence: 99%
“…The collagen chains are encoded by at least 17 genes. The collagen type III α1 (COL3A1) gene encodes type III collagen and might be associated with hiatus hernia formation 38 . Collagen type XXIII α1 (COL23A1) gene is probably linked to scrotal hernia development in pigs 39 .…”
Section: Studies On Collagen Synthesismentioning
confidence: 99%
“…The major findings of the study were that a single nucleotide polymorphism within the gene encoding for collagen type III (COL3A1) was associated with GORD in both sexes and hiatal hernia in males. In keeping with these findings, immunohistochemistry of oesophageal biopsies showed increased connective tissue abnormalities (ie, collagen type III positive staining) in GORD patients compared with asymptomatic controls 1. GORD has been defined by symptoms, endoscopy and pH monitoring data 2 3.…”
mentioning
confidence: 58%
“…With interest we read the article by Asling et al ,1 entitled “Collagen type III (COL3A1) is a gastro-oesophageal reflux disease (GORD) susceptibility gene and a male risk factor for hiatus hernia”, which has been published in a recent issue of Gut . The major findings of the study were that a single nucleotide polymorphism within the gene encoding for collagen type III (COL3A1) was associated with GORD in both sexes and hiatal hernia in males.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings showed that COL3A1 was overexpressed in families with GERD and hiatal hernia. Although it was noted to be overexpressed only in males with both GERD and hiatal hernia, the findings suggest that abnormal collagen deposition may alter the integrity of the periesophageal ligaments, thereby contributing to hiatal hernia formation [19].…”
Section: Collagenmentioning
confidence: 98%